The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1111/j.1742-1241.2006.01003.x
|View full text |Cite
|
Sign up to set email alerts
|

The emerging pandemic of obesity and diabetes: are we doing enough to prevent a disaster?

Abstract: Obesity is growing into a global epidemic and alarming trends are seen in Asian countries. Although obesity is defined by body mass index (BMI), waist circumference has emerged as a more specific marker of metabolic risk. BMI and waist circumference thresholds vary between ethnicities and values are lower for Asian populations. Asians are at an increased risk of developing diabetes and early death from cardiovascular complications at lower levels of BMI and waist circumference. Obesity, especially central obes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(52 citation statements)
references
References 43 publications
1
51
0
Order By: Relevance
“…Obesity and DM have reached worldwide pandemic proportions, 23 with one third of adults in the United States classified as obese (body mass index [BMI] ‡ 30 kg/m 2 ) 24,25 DM, CVD, hypertension, stroke, dyslipidemia, and osteoarthritis are some of the obesity-related diseases that decrease the life span.…”
Section: Obesitymentioning
confidence: 99%
“…Obesity and DM have reached worldwide pandemic proportions, 23 with one third of adults in the United States classified as obese (body mass index [BMI] ‡ 30 kg/m 2 ) 24,25 DM, CVD, hypertension, stroke, dyslipidemia, and osteoarthritis are some of the obesity-related diseases that decrease the life span.…”
Section: Obesitymentioning
confidence: 99%
“…Obesity is associated with an increased risk for type 2 diabetes [1]. In severely obese individuals, surgically induced weight loss significantly lowers the incidence of type 2 diabetes [2][3][4] and primary prevention trials have shown that moderate weight reduction can reduce the risk for type 2 diabetes in obese individuals with impaired glucose tolerance [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…he world is in the grip of a diabetes and obesity epidemic (1). The reasons for this are complex, but modern lifestyles that allow the avoidance of physical activity are thought to have played a major role (2).…”
mentioning
confidence: 99%